2017
DOI: 10.1371/journal.pone.0179252
|View full text |Cite
|
Sign up to set email alerts
|

Pitch contour impairment in congenital amusia: New insights from the Self-paced Audio-visual Contour Task (SACT)

Abstract: Individuals with congenital amusia usually exhibit impairments in melodic contour processing when asked to compare pairs of melodies that may or may not be identical to one another. However, it is unclear whether the impairment observed in contour processing is caused by an impairment of pitch discrimination, or is a consequence of poor pitch memory. To help resolve this ambiguity, we designed a novel Self-paced Audio-visual Contour Task (SACT) that evaluates sensitivity to contour while placing minimal burden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…This may be due to compensation for the reduced availability of pitch cues for amusic individuals, leading to increased reliance on non-pitch auditory cues. This interpretation would be in agreement with the recent finding that amusics are less impaired at audiovisual integration with brightness or loudness than with pitch (Lu et al, 2017). In the present study, however, their lack of impairment was observed within a single dimension, rather than in the context of audiovisual integration.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This may be due to compensation for the reduced availability of pitch cues for amusic individuals, leading to increased reliance on non-pitch auditory cues. This interpretation would be in agreement with the recent finding that amusics are less impaired at audiovisual integration with brightness or loudness than with pitch (Lu et al, 2017). In the present study, however, their lack of impairment was observed within a single dimension, rather than in the context of audiovisual integration.…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, it has also been suggested that amusia affects the perception and memory of musical timbre (Marin, Gingras, & Stewart, 2012;Tillmann et al, 2009), which might be explained by a deficit in spectral pitch. Nevertheless, in the context of cross-modal integration between vision and audition, some recent evidence (Lu, Sun, Ho, & Thompson, 2017) has suggested that the integration of contour cues (presented in either auditory or visual modality) may be less impaired in amusics for auditory brightness and loudness than it is for pitch. It remains unknown, however, whether amusics' deficits in contour perception are restricted to pitch in the absence of any audiovisual integration task.…”
Section: Introductionmentioning
confidence: 99%
“…The third main finding of our study is that unlike normals, amusics demonstrated a dysfunctional HMS in the understanding of musical meaning, which is in agreement with our prior EEG study that reported the absence of an N400 effect in processing musical meaning in amusia [47]. The failure to derive musical meaning from pitch change direction confirmed that amusia is indeed a pitch-related disorder, including pitch perception [e.g., 50,51,104], tonal functional cognition [105][106][107], and emotion perception [108][109][110][111]. Although impaired pitch discrimination and memory in amusia is related to abnormal activity changes in the right IFG as well as decreased functional connectivity between the right IFG and the right auditory cortex [112][113][114], our study further indicates that impaired musical meaning understanding in amusia is associated with aberrant brain activity in the left parietofrontal cortices.…”
Section: Discussionsupporting
confidence: 90%
“…Along the same line, our recent behavioral studies showed that, compared with controls, people with congenital amusia perform worse on spatial representation and mental rotation task [25]. Similar studies also suggested that pitch processing may rely on cognitive mechanisms that are similar to those used for spatial processing [26,27], although, some other researchers failed to find an association between congenital amusia and deficits in spatial processing [28,29]. To date, investigations into whether congenital amusics have other kinds of non-musical deficiencies have been limited to the examination of language ability and spatial ability.…”
Section: Introductionmentioning
confidence: 75%